PEMBACAAN DEKONSTRUKSI CERPEN "ZINA" KARYA PUTU WIJAYA - Ronidin Ronidin (Puitika, 2015)
This article is aimed at revealing the paradox meaning of some events in short story “Zina” written by Putu Wijaya. The short story “Zina” is chosen to be analyzed because it describes some unique events in the short story and they are beyond of common logic. The analysis of this short story is conducted by using deconstruction approach. It is a qualitative research and it is described descriptively. Based on the result of the analysis, it is found that the unique events that are found in short story “Zina” which seems paradox with common sense, in fact there is a truth inside. A wife who ask permission to her husband to have an affair with somebody else, a forbidden affair that is done in front of palace and bus way line, and an open affair in front of public are unique events that hide many paradox meanings. Some of paradox meanings are; the importance of husband’s admittance for a wife, the importance of new atmospheres in a family, and the importance of governing social awareness.    Keywords:  short story, paradox, approval, wife, husband, adulteryABSTRAK Artikel ini bertujuan untuk mengungkapkan makna paradok beberapa peristiwa dalam cerpen “Zina” karya Putu Wijaya. Cerpen “Zina” dipilih untuk dianalisis karena menggambarkan beberapa peristiwa aneh dan di luar logika biasa. Analisis terhadap cerpen ini akan dilakukan dengan menggunakan pendekatan dekonstruksi. Analisis bersifat kualitatif dan disajikan secara deskriptif. Berdasarkan hasil analisis data, diperoleh gambaran bahwa keanehan-keanehan yang terdapat dalam cerpen “Zina”, yang seolah-olah bertentangan dengan pendapat umum, pada kenyataannya mengandung kebenaran. Istri yang minta izin suami untuk berzina, perzinaan pasangan suami istri di depan istana dan lajur bus way, dan perzinaan terbuka suami istri itu di depan umum dan ditonton banyak orang merupakan peristiwa aneh yang menyembunyikan makna paradok. Di antara makna paradok itu adalah pentingnya izin suami bagi istri, pentingnya suasana-suasana baru dalam keluarga, dan pentingnya membangun kepedulian sosial.   Kata Kunci:  cerpen, paradoks, izin, istri, suami, zina